Revised Interpretation of the Origin of the pSC101 Plasmid - Cohen, Stanley N. (1977)
Data are presented indicating that the pSC101 plasmid was not derived by recircularization of a mechanically sheared fragment of R6-5 plasmid deoxyribonucleic acid, as was originally believed.